A Psychological Pressure in Novels: “MENYUSU CELENG” - Setya Adi, Atanasius Raka; Tyas, Theresia Prias Hayu Purbaning (Indonesian Journal of Educational Counseling, 2024)
The content of the research aims to: 1) find out what factors or causes of psychological pressure are contained in the novel "Menyusu Celeng" 2) knowing the forms of psychological pressure contained in the novel "Menyusu Celeng". 3) find out what the effects of psychological pressure are contained in the novel " Menyusu Celeng". In this study, the researcher used the mixed method used to analyze documents in the novel "Menyusu Celeng". The researcher use Qualitative Data Analyze Miner (4.0) as an application to help classify and analyze data. Based on the results of the data analysis, it was found: 1) The psychological pressure factor that has the greatest percentage in the novel "Menyusu Celeng" derived from the environment around a person or individual. 2) The greatest impact of psychological pressure identified in the novel "Menyusu Celeng" the emotion which is also divided into positive emotions (eustress) and negative emotions (distress). 3) Psychological pressure received by individuals is most revealed in the novel " Menyusu Celeng" with aggressive behavior.